Production of Robusta Instant Coffee Powder with Variation of Fillers - Miftahul Wahidatun Ni’mah; Umar Hafidz Asy'ari Hasbullah; Endang Is Retnowati (AGROINTEK, 2021)
Instant coffee powder is a downstream product of coffee processing. The purpose of this research was to study the effect of fillers on the physical, chemical, and sensory properties of instant coffee powder. This study was used Robusta coffee which was roasted at medium to dark level. The fillers used were maltodextrin and dextrin. The instant coffee powder was made by crystallization and drying techniques with a cabinet dryer. The results showed that the difference between the two fillers did not affect the physical properties of instant coffee powder such as yield, pH, solubility, brightness (L*), and yellowishness (b*). Meanwhile, the chemical properties of water content showed a significant difference between the two treatments. The sensory properties of the two treatments have a description of the color tends to be bright, slightly brown, the taste was quite bitter, slightly sweet, quite sour, the aftertaste was medium sour, the aftertaste was low in smoke, the aftertaste was quite detectable, the aroma of coffee was medium, slightly sweet, and slightly caramel-flavored. The instant coffee powder has the potential to be developed as a coffee flavoring preparation for food products.